A qualitative approach to understanding the role of lecture capture in student learning experiences. Issue 4 (8th August 2017) - Hall, Gareth; Ivaldi, Antonia
Abstract: Lectures continue to be the dominant form of university teaching, and lecture capture technologies are tentatively taken up to support this form of delivery, rather than being used as a viable alternative. Much of the previous research, however, has been self-reports or survey-based, with far less attention given to qualitative explorations. This study aims to bridge this gap by using qualitative methods in order to examine students' experiences of lecture capture provisions within the context of their own learning by utilising six focus groups to generate data. Thematic analysis was used to understand group opinions and experiences of lecture capture within university teaching. Two conceptual themes emerged: enhancing the learning environment and working and learning strategically. Results show that the value of lecture capture provisions could not be fully evaluated by students without considering their current learning environments. The main positive function of lecture capturing was to alleviate negative perceptions of lectures as a learning event, but it also provided students an opportunity to learn strategically. The extent to which lecture capturing develops and enhances the learning experience is discussed. Recommendations for how universities could utilise lecture capturing are proposed.